ENVIRONMENTAL FACTORS AND SELF CONCEPT OF THE STREET CHILDREN - Kurnajati, Sandy; Fawzie, Zeptien Chrystalia (Jurnal Penelitian STIKES Kediri, 2012)
The phenomenon of street children actually have been grown for long time, but today it becomes the world's attention, as long as the increasing number of street children in the big cities around the world. A hard life, the need for independent life, the less attention from the parents, the environment that is not conducive, and the lack of opportunity to school are factors that affect the self-concept on the street child. The purpose of this study was to analyze the relationship between environmental factors and the self concept of street children aged 12-18 years in Kediri city. The design of this study was an analytic cross sectional. The population in this study were all street children in the city of Kediri. The amount of sample that is determined were 30 respondents using quota sampling. The independent variables was the environmental factors and the dependent variable was the self concept. The data were collected by questionnaires and analyzed Mann Whithney statistical test with significance level α <0.05.From the results of data analysis known that street children had not good environment, had not good self-image, have sufficient ideal of self, a good role, the good identity, sufficient of the self-concept. The results of Spearman's Rho statistical tests obtained p = 0.143, so there is no relationship between independent variables and the dependent variable. The conclusion is that the environmental factors haven’t relation with the self concept of street children aged 12-18 years in Kediri city, although the street children has a good environment but they have a negative self concept.